On the prevalence of ectoparasites in Rui (Labeo rohita) in greater Mymensingh region, Bangladesh (Bangladesh Journal of Zoology, 2025)
The study investigated the prevalence of ectoparasites in Rui, Labeo rohita collected from greater Mymensingh, Bangladesh, between July 2022 and June 2023. A total of 960 samples were randomly collected to identify the ectoparasites using a microscope, and in the second phase, direct smears were prepared from probable lesions. In this study, a total of ten different ectoparasites were identified, including myxozoans (Myxobolus sp., Thelohanellus sp., and Henneguya sp.); ciliophorans (Trichodina sp., Tripertiella sp., and Ichthyophthirius multifilis); monogeneans (Dactylogyrus sp. and Gyrodactylus sp.); and crustaceans (Ergasilus sp., Argulus sp., and Lernea sp.). Myxozoans and ciliophorans were more prevalent among these parasites, followed by the monogeneans and crustacean parasites. The highest ectoparasitic prevalence (35.04%) was recorded from January to February, while the lowest (6.67%) was from July to August. This study indicates that winter was more favorable for the outbreaking of these ectoparasites in L. rohita cultured using carp polyculture system earthen ponds in greater Mymensingh, Bangladesh. Carp polyculture farmers are suggested to take preventive measures like avoiding the deterioration of water quality, high stocking density, and application of lime and common salt in inhibiting the outbreak of these ectoparasites for better production, economic return, and sustainability of Indian major carp culture in Bangladesh.Bangladesh J. Zool. 53(1): 67-77, 2025